Therapeutic pathomorphosis of advanced NSCLC as a criteria for effectiveness of induction chemotherapy. - Kosse V.A.; Chekan S.M.; Sukhoversha O.A.; Bilen’kiy I.V.; Lisogub V.V. (Морфологія, 2007)
The aim of the study was the investigation of therapeutic pathomorphosis (ThP) of non-small cell lung cancer (NSCLC) and definition of its role as a criteria for effectiveness of induction chemotherapy (ICT). In the context of investigation there were 152 patients with IIIA st. NSCLC, being treated with ICT (102 pts) and without it (50 pts). The analysis of qualitative and quantitative pathomorphological changes in tumors after platinum-based ICT was performed. Patients’ operability in the group with ICT was significantly higher than in control group (72.6% versus 56.0%) that proves the effectiveness of ICT as a method of induction influence. The ICT estimation has to be complex, that means – the clinical effect should be verified by pathomorphological studies. Under the influence of ICT in NSCLC noticed the different ThP: 1 st. – 51%, 2-3 st. – 48%, 4 st. – 1% with better response rate in low-differentiation tumor. Being influenced by ICT, the part of viable tumors’ paren-chyma and its proliferating activity has significantly decreased, that is the essential component of further prognosis. The tu-mors’ resectability correlated with the level of its ThP, which serves the basis for necessity of reaching the maximal clinical effect of ICT.